Experiencia y Afrontamiento del Estrés Social, Económico, Laboral y Familiar en la Vida Cotidiana de un Grupo de Docentes de Secundaria de una Institución Educativa de la Ciudad de Bogotá: El Papel de la Inteligencia y Competencias Emocionales como Estrategias de Afrontamiento (2023)
The present research aimed to analyze how individuals, specifically teachers aged between 35 and 71 years old, experience and cope with social, economic, work-related, and family stress through narratives constructed from their own experiences. The study adopts a qualitative approach, employing a semi-structured interview and a field diary as data collection techniques. In this line of thought, the findings reveal a significant variability in stress experiences among the participants, indicating a considerable diversity in how the study participants experience and cope with stress. There is no uniform or homogeneous response to stress among the participants.